Genetic structure and population differentiation of endangered Scrophularia takesimensis (Scrophulariaceae) in Ulleung Island, Korea - Ma, S.M., Soonchunhyang University, Asan, Republic of Korea; Lim, Y.S., Soonchunhyang University, Asan, Republic of Korea; Na, S.T., Soonchunhyang University, Asan, Republic of Korea; Lee, J., Soonchunhyang University, Asan, Republic of Korea; Shin, H.C., Soonchunhyang University, Asan, Republic of Korea (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2011)
As a part of the on-going effort to conserve endangered Scrophularia takesimensis Nakai in Korea, its genetic structure and diversity from 3 population, consisted of 14 subpopulations in Ulleung Island were analyzed using RAPD band patterns. Out of 60 primers tested, 33 generated amplified bands with its genome, including 149 polymorphic and 67 monomorphic bands. The highest number (146) was found in northern population, especially, 64 in HY subpopulation; the smallest (40) in eastern population. An examination of its genetic structure with AMOVA revealed that about 60% of all variations could be assigned to among subpopulations within populations. Population differentiation among populations and subpopulations is seriously going now because of habitat fragmentation due to human activities, such as road and small port construction. Although the habitats of S. takesimensis in Ulleung Island, Korea are disappeared at an alarming rate, significant levels of genetic variation still exist at species level, and population level, especially northern population. Therefore, three conservation strategies should be needed urgently; 1) preservation of populations as it stands, 2) establishment of recovery plan to connect population and subpopulations genetically, and 3) long-term monitoring.